Changes in Prevalence, Outcomes, and Help‐seeking Behavior of Chronic Pain in an Aging Population Over the Last Decade. Issue 5 (13th October 2016) - Cheung, Chi Wai; Choi, Siu Wai; Wong, Stanley Sau Ching; Lee, Yvonne; Irwin, Michael Garnet
Abstract: Background: Chronic pain is expected to increase as the population ages. This study aimed to investigate the changes in prevalence, patterns, and help‐seeking behavior of chronic pain and prevalence of neuropathic pain of an aging population in Hong Kong. Methods: A cross‐sectional, telephone interview with a structured questionnaire was conducted in a randomly selected sample of adults with acute or chronic pain of any kind in the general population to estimate the prevalence of chronic and neuropathic pain, and to describe sociodemographics and help‐seeking behavior. Results were compared with a similar study conducted in 1999. Results: Totally, 1, 570 people were interviewed. Chronic pain was experienced by 28.7% of all respondents, compared to 10.8% in 1999. Joint (45.5%), muscle (27.1%), and back (25.2%) pain were the most common, similar to findings in 1999. Of those with chronic pain, 83.1% reported pain in more than one body site (63.4% in 1999, P = 0.0023). More respondents reported their average pain as being intense (51.57% vs. 33.0% in 2013 and 1999, respectively, P = 0.0098). A downward trend of respondents taking medications for chronic pain (34.9% in 2013 vs. 47.6% in 1999, P = 0.019) was seen. Neuropathic pain was present in 9.03% of the population and 14.7% of chronic pain sufferers. Conclusion: The prevalence of neuropathic pain in Hong Kong is high and is described here for the first time. The number of chronic pain sufferers has tripled in the past decade. Significant changes in the patterns and help‐ seeking behavior of chronic pain sufferers are also seen.